Optimization of Nutritive Factors in Culture Media for Growth and Tropane Alkaloid Production from Anisodus acutangulus Hairy Roots - Qijia Liu, Lijie Cui, Yingying Guo, Xiaoling Ni, Yan Zhang, Guoyin Kai (Journal of Applied Pharmaceutical Science, 2013)
Anisodus acutangulus hairy roots were grown in N6 medium which was optimal for growth and alkaloid production. The cell biomass and alkaloid yield reached 2.7 g l-1 and 3.9 mg l-1 (dry weight) respectively in sucrose medium, higher than those obtained in other carbon source media. 90 mM nitrogen (NH4+/NO3- = 4:1) gave the highest cell yield (4.5 g l-1) and the maximum alkaloid production (9.9 mg l-1). The cell yield (4.1 g l-1) of hairy roots grown at pH 6.5 was 2 times higher than that at pH 4.5. However, the maximum alkaloid production (7.2 mg l-1) was yielded at pH 4.5.
Keywords: Alkaloid production, Anisodus acutangulus,Hairy root